Urban Birds Using Insects on Front Panels of Cars - Jukka Jokimäki; Marja-Liisa Kaisanlahti-Jokimäki (Birds, 2023)
Urbanization influences the food availability and quality for birds in many ways. Although a great amount of food for birds is provided incidentally or intentionally in urban areas, the quantity of insect-based food can be reduced in cities. We studied the role of one artificial food source, insects smashed on the front panels of cars, in Finland, and more specifically in the city of Rovaniemi, by conducting questionnaire research, searching for data from databases and performing a field study. Our results indicated that a total of seven bird species have been detected using insects on the front panels of cars in Finland. However, this behavior is not yet common since about 60% of responders to the questionnaire stated that this behavior is currently either rare or very rare. Most of the observations identified House Sparrows, followed by the White Wagtail or the Eurasian Jackdaw. Only a few observations identified the Eurasian Tree Sparrow, the Hooded Crow, the Great Tit and the Eurasian Magpie. The phenomenon was distributed quite widely across Finland, except in the case of the Eurasian Jackdaws, for which observations were restricted only to the southern part of the country. The first observation was made about the House Sparrow in 1971, followed by the White Wagtail (1975), Hooded Crow (1997), Eurasian Jackdaw (2006), Eurasian Tree Sparrow (2011), Eurasian Magpie (2019) and Great Tit (2022). The species using this food source are mainly sedentary urban exploiters, such as corvids and sparrows, that have been previously reported to have several different types of innovative behaviors. Most of the observations were conducted in urban parking sites of hypermarkets, and no observations were made in residential areas. Most of the foraging observations were made during the end phase of the breeding season, partly supporting the extra need for high-quality insect-based food for nestlings and fledglings. Our observations indicate that this behavior is not yet common and widespread among species.